Exploring the Impact of Teacher Social Responsibility on Student Development and Community Engagement (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article presents the results of the study of Exploring the Impact of Teacher Social Responsibility on Student Development and Community Engagement. The work was carried out with students of advanced training courses on the basis of Dongshin University. It was attended by teachers of Dongshin University, The study showed that in recent years, in the conditions of implementation of new educational standards, the intensity of work of the teacher has increased dramatically, There are new types of professional activities, new professional duties and roles, as well as increased qualification requirements for the teacher.